The role of SARS-CoV-2 N protein in diagnosis and vaccination in the context of emerging variants: present status and prospects - Song, Wanchen; Fang, Zhongbiao; Ma, Feike; Li, Jiaxuan; Huang, Zhiwei; Zhang, Yanjun; Li, Jianhua; Chen, Keda (Frontiers in Microbiology, 2023)
Despite many countries rapidly revising their strategies to prevent contagions, the number of people infected with SARS-CoV-2 continues to surge. The emergent variants that can evade the immune response significantly affect the effectiveness of mainstream vaccines and diagnostic products based on the original spike protein. Therefore, it is essential to focus on the highly conserved nature of the nucleocapsid protein as a potential target in the field of vaccines and diagnostics. In this regard, our review initially discusses the structure, function, and mechanism of action of N protein. Based on this discussion, we summarize the relevant research on the in-depth development and application of diagnostic methods and vaccines based on N protein, such as serology and nucleic acid detection. Such valuable information can aid in designing more efficient diagnostic and vaccine tools that could help end the SARS-CoV-2 pandemic.